Antimicrobial and Cytotoxic Activities of the Extracts of Glochidion multiloculare (Journal of Science Foundation, 2013)
The current study was designed to investigate the antimicrobial and cytotoxic activities of methanol extract (MEGM), petroleum ether fraction (PEFGM), carbontetrachloride fraction (CTFGM), chloroform fraction (CFFGM) and aquous fraction (AQFGM) of stem bark of Glochidion multiloculare (Euphorbiaceae). Antimicrobial activity was evaluated by disc diffusion method and cytotoxic activity by brine shrimp lethality bioassay. In case of antimicrobial screening the CFFGM showed moderate inhibitory activity against B. subtilis having the zone size 12 mm and against Escherichia coli and Escherichia coli were 11 mm, while in the brine shrimp lethality bioassay, the petroleum ether soluble fraction revealed the highest cytotoxicity having LC50 of 3.11 g/ml. DOI: http://dx.doi.org/10.3329/jsf.v10i1.16273 J Sci Foundation, January-June 2012;10(1):1-11